2021
DOI: 10.1101/2021.11.26.470180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental analysis and biaxial biomechanical behaviour of ex-vivo sheep trachea

Abstract: PurposeThe purpose of this study is to investigate the mechanical behaviour of the tracheal tissue under biaxial tensile loading. Furthermore, the study examines the material properties of the tissue through a study of the model parameters for six constitutive models.Materials and methodsThe fourteen (n = 13) trachea sheep (Vleis Merino) pieces of tissues measured to be ~ 30 × 20 mm where only the effective area subjected to engineering strain was ~ 25 × 16 mm. In this study, we assume that the tracheal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This would in turn ensure the proper fiber kinematics influencing the tissue's mechanical response. To the best of our knowledge only one study has been reported to have conducted biaxial tension testing on tracheal tissue (Nemavhola et al, 2021). However, they do not test individual tissue layers, thus upholding the novelty of our test results.…”
Section: Mechanicsmentioning
confidence: 57%
“…This would in turn ensure the proper fiber kinematics influencing the tissue's mechanical response. To the best of our knowledge only one study has been reported to have conducted biaxial tension testing on tracheal tissue (Nemavhola et al, 2021). However, they do not test individual tissue layers, thus upholding the novelty of our test results.…”
Section: Mechanicsmentioning
confidence: 57%